2019
DOI: 10.3389/fnagi.2019.00278
|View full text |Cite
|
Sign up to set email alerts
|

Elevations in Serum Dickkopf-1 and Disease Progression in Community-Dwelling Older Adults With Mild Cognitive Impairment and Mild-to-Moderate Alzheimer’s Disease

Abstract: Background: Disruption of Wnt signaling has been implicated in dysfunctional synaptic plasticity, the degree of which correlates with Alzheimer’s disease severity. We sought to examine whether serum levels of Dickkopf-1 (Dkk-1), a Wnt antagonist, are associated with global disease progression in older adults with mild cognitive impairment (MCI) and mild-to-moderate AD.Methods: We prospectively followed 88 older adults with MCI and mild-to-moderate AD attending a Memory Clinic. Cognitive performance, functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The fact that the molecular fluid biomarker signature between normal ageing and AD is different (e.g., [184]) would support qualitative differences between the two. In this context, Wnt signalling components are yet to be firmly established as fluid biomarkers for AD, although recent studies have suggested serum DKK1 as a predictor of deteriorating disease both in AD and acute ischemic stroke patients [261,262].…”
Section: Are the Wnt Changes Seen In Ad Simply An Exacerbated Consequence Of Ageing?mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the molecular fluid biomarker signature between normal ageing and AD is different (e.g., [184]) would support qualitative differences between the two. In this context, Wnt signalling components are yet to be firmly established as fluid biomarkers for AD, although recent studies have suggested serum DKK1 as a predictor of deteriorating disease both in AD and acute ischemic stroke patients [261,262].…”
Section: Are the Wnt Changes Seen In Ad Simply An Exacerbated Consequence Of Ageing?mentioning
confidence: 99%
“…Similarly, can DKK1 be detected in cerebrospinal fluid (CSF)? Further establishing DKK1 CSF or serum biomarkers [261,262] would be valuable in understanding where DKK1 fits in the pathophysiology of AD, as well as being a target biomarker for evaluating DKK1 therapeutics. It would also have the potential to enable precision medicine by identifying those patients who have upregulated DKK1.…”
Section: Looking Forward: Does Wnt Signalling Offer Opportunities For New Therapies For Ad?mentioning
confidence: 99%
“…In the present study, we observed a reduction in both Wnt5a and its major receptor, FZD2, in the hippocampus of AD mice. Studies have demonstrated a significant upregulation in the expression of Wnt signaling inhibitor proteins (such as DKK-1, SFRP-1, and SFRP-2) in postmortem AD brain and transgenic AD mouse models [ 52 , 53 ].This upregulation effectively suppresses the Wnt signaling pathway in Alzheimer's disease (AD). Consequently, there is a subsequent decrease observed in the expression levels of WnT-related proteins (e.g., wnt5a, wnt3a) and various intracellular related proteins (e.g., FZD2, DVL2, GSK3β).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Inestrosa et al showed that Wnt/β-catenin is involved in regulating synaptic plasticity and maintaining BBB integrity; Inestrosa et al also found that activated WNT/β-catenin signaling prevented neural toxicity caused by Aβ, that WNT/β-catenin participates in a normal degree of tau phosphorylation and in learning and memory, and that WNT/β-catenin dysfunction results in Aβ production and aggregation [ 74 ]. Tay et al followed 14 subjects with MCI and 74 with mild-to-moderate AD and measured the scores for the clinical dementia sum of boxes (CDR-SB) at baseline and after one year and assessed the correlations between changes in the CDR-SB and serum levels of Dickkopf-1 (Dkk-1), which is an antagonist of Wnt [ 75 ]. Decreased levels of Wnt as shown by the increase in Dkk-1, which is an antagonist of Wnt/β-catenin, were significantly associated with progressively higher CDR-SB scores (indicating more impairment) among patients with AD but not among patients with MCI.…”
Section: Wnt/β-catenin and Admentioning
confidence: 99%